OBSTACLES IN LAW ENFORCEMENT AGAINST PERPETRATORS OF SEXUAL ABUSE INFLUENCED BY PORNOGRAPHY IN TERRITORY OF BENGKULU DISTRICT COURT - Ainul Mardiati; Herlambang Herlambang; M. Abdi (Universitas Bengkulu, 2020)
Indigenous village is important, therefore, it is required the establishment of indigenous villagein the respective regencies in Indonesia. To form the indigenous village needs to see some supportingaspects.One of sub-district which has a supporting aspect in the formation of indigenous villages in North Bengkulu is Enggano District. The research objective isto know and analyze the obstacles faced in implementing Law No. 6 of 2014 in the establishment of indigenous village in Enggano District of North Bengkulu. The methodology used is empirical juridical approach, byusing qualitative analysis. The result study showed that the obstacles encountered in the implementation of Law No. 6 of 2014 on Village in the establishment of the indigenous village in Enggano District of North Bengkulu consisted of two factors:Internal and external factors.